Proof Of Grant That Violates Legitieme Portie According To Civil Code - Mahalia Nola Pohan, Nita Nilan Sry Rezki Pulungan (NOMOI Law Review, 2020)
Grantas mentioned in Article 1666 of the Civil Code, is